An investigation on oxidation/carburisation of 9Cr-1Mo steel heat exchanger tube in an AGR environment. (4th May 2018) - Yan, Sabrina; Doak, Scott; Thomson, Rachel; Higginson, Rebecca
Abstract: 9Cr–1Mo steels have been used extensively in the power generation industry. In this study, a wide range of experimental samples exposed at different times and temperatures in a CO2 environment were analysed to look at the development of the metal and oxides over time. The main objective of this work was to obtain a better understanding of the carburisation and oxidation behaviour of 9Cr 1Mo steels as a function of temperature/time, with special attention paid to the transition from protective to breakaway oxidation. In addition, experiments were also carried out to investigate any links between oxidation transition and carburisation behaviour of these materials.